2019
DOI: 10.17853/1994-5639-2019-5-87-112
|View full text |Cite
|
Sign up to set email alerts
|

About relevance of fundamentalisation of mathematical training of students of the pedagogical directions during the digital era

Abstract: Introduction. The era of post-industrial society of knowledge differs from the previous socio-economic period in many important aspects: total digitalisation, automation and robotisation, and furthermore, cross-disciplinary integration of various scientific fields, among which mathematics is of particular relevance. Over the last decades, the language, tools and methods of the digital era have emerged as the basic universal research tools in physics, biology, chemistry, and engineering, organisation of product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…For example, in 2017, Class Central reported that 78 million students took 9.4 thousand e-learning courses at more than 800 universities in the world [22]. Recent advances in e-learning, analytics and data mining tools allow the use of detailed data to understand and support teaching and learning [23]. It is now possible to conduct experiments in education and support efforts to achieve personalized learning goals.…”
Section: Visualization Of Student Involvement In the Educational Procmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in 2017, Class Central reported that 78 million students took 9.4 thousand e-learning courses at more than 800 universities in the world [22]. Recent advances in e-learning, analytics and data mining tools allow the use of detailed data to understand and support teaching and learning [23]. It is now possible to conduct experiments in education and support efforts to achieve personalized learning goals.…”
Section: Visualization Of Student Involvement In the Educational Procmentioning
confidence: 99%
“…It is now possible to conduct experiments in education and support efforts to achieve personalized learning goals. Learning analytics and visualization allow evaluating and comparing content modules, teaching methods, and course design in order to optimize learning outcomes and competencies based on the goals of both individual students and universities [23]. The combination of learning and visualization analytics provides new opportunities for identifying student core competencies, skills, and the ability to adapt to changes.…”
Section: Visualization Of Student Involvement In the Educational Procmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained mathematical information, facts should be the starting point in their professional, computational, social, communicative practice. The authors negatively relate to the growing imbalance between the necessary fundamental mathematical training for graduates and the implemented model of mathematical education at school (Perminov, Gadjiev & Abdurazakov, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, we conclude that some researchers have negative attitude to the use of digital technologies in mathematical activity, stating that computational activity is reduced to automating work with a calculator, spreadsheet editor, etc. (Nagornaya, 2015;Perminov, Gadjiev & Abdurazakov, 2019). Failure to perform simple mental mathematical operations leads to a fall in the general information culture.…”
Section: Literature Reviewmentioning
confidence: 99%